Familial hypertrophic cardiomyopathy with midventricular obstruction associated with MYH7, FHOD3 and BAG3 gene variants: a case report - S. E. Andreeva; M. O. Marusova; M. A. Bortsova; A. A. Kostareva (Российский кардиологический журнал, 2024)
Introduction. Hypertrophic cardiomyopathy (HCM) with midventricular obstruction (MVO) represents a subgroup of increased risk of adverse outcomes. It contributes to development of apical aneurysm, which is an anatomical substrate for the development of malignant arrhythmias, thromboembolism, as well as progression to end stage systolic heart failure. Genetic causes of HCM with MVO are poorly described in Russian and foreign literature.Brief description. We present a case of a 54-year-old female patient with a familial HCM with isolated MVO and rare missense variants in the MYH7, FHOD3 and BAG3 genes. The clinical performance was represented by a paroxysmal atrial fibrillation, as well as episodes of nonsustained ventricular tachycardia.Discussion. According to the European HCM Risk-sudden cardiac death (SCD) calculator, the patient was stratified into an intermediate risk group. However, we also took into account gadolinium-enhanced myocardial areas according to magnetic resonance imaging, as well as no conditions for MVO surgery. This was key in determining the indications for a cardioverter-defibrillator implantation within primary SCD prevention.